2013
DOI: 10.21273/hortsci.48.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rapid Consecutive Postharvest 1-Methylcyclopropene Treatments on Fruit Quality and Storage Disorders in Apples

Abstract: The objective of this study was to investigate the effects of rapid consecutive 1-methylcyclopropene (1-MCP) treatments on apple quality and disorders in storage. ‘McIntosh’ and ‘Spartan’ apples were harvested twice from commercial orchards and 1-MCP (1 μL·L−1) was applied postharvest either 1 day after harvest or 1 and 2 days after harvest. Similar fruit from both cultivars were also not treated with 1-MCP, plus an additional treatment of 2 μL·L−1 (double rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Despite the absence of harvest date effects on flesh browning incidence, the results supported previous research showing that incidence of the disorder can be increased by 1-MCP treatment (Watkins, 2008;DeEll and Ehsani-Moghaddam, 2013;Watkins and Nock, 2005;Jung and Watkins, 2011), and that disorder development is greater in the stem end than calyx end tissues (Lee et al, 2012a). Therefore, these data provided an opportunity to investigate the potential involvement of PPO and POX activities and total phenolic concentrations in browning of tissue from different parts of the fruit and in response to 1-MCP.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the absence of harvest date effects on flesh browning incidence, the results supported previous research showing that incidence of the disorder can be increased by 1-MCP treatment (Watkins, 2008;DeEll and Ehsani-Moghaddam, 2013;Watkins and Nock, 2005;Jung and Watkins, 2011), and that disorder development is greater in the stem end than calyx end tissues (Lee et al, 2012a). Therefore, these data provided an opportunity to investigate the potential involvement of PPO and POX activities and total phenolic concentrations in browning of tissue from different parts of the fruit and in response to 1-MCP.…”
Section: Discussionsupporting
confidence: 85%
“…The shorter the time between preharvest 1-MCP treatment and harvest, the firmer the fruit and the lower the IEC for 'Delicious' apple, although there was no direct effect of the ethylene concentration on firmness during the storage of fruit treated with preharvest and postharvest 1-MCP (Elfving et al, 2007;Lee et al, 2016). Postharvest 1-MCP treatment maintained higher TA than no treatment during cold storage as the IEC was suppressed, but it did not affect the responses of SSC (DeEll and Ehsani-Moghaddam, 2013). Loss of acidity is similar to starch degradation, with low dependency on, but high sensitivity to, ethylene (Johnston et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…ethylene perception, is widely used by apple industries after harvest to maintain fruit quality attributes, such as fruit firmness, acidity, sweetness, juiciness, and crispiness (Bai et al, 2005;DeEll et al, 2007;DeLong et al, 2004;Larrigaudi ere et al, 2008;Jung and Lee, 2009;Watkins et al, 2000). Treatment with 1-MCP can reduce the development of certain physiological disorders, such as senescent breakdown (DeLong et al, 2004;Jung and Watkins, 2008), diffuse flesh breakdown (Lee et al, 2016), core browning (DeEll and Ehsani-Moghaddam, 2013), fruit cracking (Lee et al, 2016), flesh breakdown , peel greasiness (Dong et al, 2012), and superficial scald (Lurie and Watkins, 2012). However, 1-MCP can increase the incidence of diffuse skin browning (Larrigaudi ere et al, 2010), flesh browning Watkins, 2008), radial stem-end flesh breakdown (Lee et al, 2016), and CO 2 injury (DeEll et al, 2003;Fawbush et al, 2008;Zanella, 2003).…”
mentioning
confidence: 99%
“…The impact 1-MCP has on the fungal decay process have been variable. Studies have shown that 1-MCP may decrease (Cameldi et al, 2016;DeEll and Ehsani-Moghaddam, 2013;Gago et al, 2015;Li et al, 2017;Saftner et al, 2003;Zhou et al, 2016) or increase (Janisiewicz et al, 2003;Leverentz et al, 2003) decay incidence in apples, whereas other studies have shown no effect on decay (DeEll et al, 2007;DeLong et al, 2004;Errampalli et al, 2012). Similarly, 1-MCP can inhibit physiological disorders such as superficial scald, senescent breakdown, and bitter pit while exacerbating others such as carbon dioxide injury, leather blotch, and diffuse skin browning (DeEll et al, 2003;Mattheis, 2008;Watkins, 2008;Watkins and Mattheis, 2019).…”
mentioning
confidence: 99%
“…The incidence of physiological disorders in apples is highly regulated by the genotype and environmental conditions before and after harvest (Watkins and Mattheis, 2019). These disorders have been reported to potentially cause losses higher than 80% of total stored fruit (DeEll and Ehsani-Moghaddam, 2013;DeLong et al, 2004;Koushesh Saba and Watkins, 2020;Lee et al, 2016;Mattheis et al, 2017). Although studies have attempted to elucidate the factors and mechanisms regulating physiological disorders in apples, there is still limited knowledge to develop efficient prediction approaches as a means to reduce losses caused by these disorders (Watkins and Mattheis, 2019).…”
mentioning
confidence: 99%